On the effect of the usury laws on the trade of lending money to the poor in Ireland - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1851)
In the course of some investigations into the condition of the poorer classes in Ireland, my attention has been directed to the state of the trade of lending money amongst them. I find that whilst the large farmers resort to regular banks to make deposits and obtain loans, there are no banks established by private enterprise for the smaller farmers and the labourers. They are forced to carry their deposits to charitable savings banks, and obtain their loans from charitable loan funds at 9.5 per cent, or else resort to local usurers at from 25 to 100 per cent. An inquiry then naturally suggests itself as to the cause of this difference. Why has private enterprise not done for the poor what it has done for the rich? The common theory which ascribes the rate of interest charged to the poor to a want of capital is manifestly fallacious, for such a cause would raise the rate of interest to the rich as well as to the poor. The cause of the phenomena to be explained must be something peculiar to loans of small sums, and especially to loans to small farmers. Such a cause is discovered by an examination of the state of the usury laws.
Read February 18th 1850. This paper was also read at the Statistical Section of the British Association, Birmingham, September, 1849.
Keywords: Pawnbrokers; Interest rates; Money lending; 314.15